2015
DOI: 10.1103/physreve.92.023008
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic simulation of a thinning liquid bridge using the dissipative particle dynamics method

Abstract: In this research, the dissipative particle dynamics method was used to investigate the problem of thinning and breakup in a liquid bridge. It was found that both the inertial-force-dominated thinning process and the thermal-fluctuation-dominated thinning process can be reproduced with the dissipative particle dynamics (DPD) method by varying the simulation parameters. A highly suspect viscous thinning regime was also found, but the conclusion is not irrefutable because of the complication of the shear viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Using various theoretical approaches, such as linear and weakly nonlinear stability analysis, approximate solutions based on one-dimensional equations and self-similarity in the vicinity of pinch-off point, and numerical simulations, the problem of thinning of liquid bridges is well understood in the case of pure (surfactant-free) liquids. The theoretical results demonstrate good agreement with numerous experimental studies. A comprehensive review on the mechanism and regularities of thinning of liquid bridges composed of pure liquids is given in refs and . It has been shown that far from the pinch-off point the thickness of the neck decreases exponentially with time .…”
Section: Introductionmentioning
confidence: 93%
“…Using various theoretical approaches, such as linear and weakly nonlinear stability analysis, approximate solutions based on one-dimensional equations and self-similarity in the vicinity of pinch-off point, and numerical simulations, the problem of thinning of liquid bridges is well understood in the case of pure (surfactant-free) liquids. The theoretical results demonstrate good agreement with numerous experimental studies. A comprehensive review on the mechanism and regularities of thinning of liquid bridges composed of pure liquids is given in refs and . It has been shown that far from the pinch-off point the thickness of the neck decreases exponentially with time .…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, in this case film rupture is solely driven by noise. This situation is analogous to the noise-driven breakup of a liquid nanojet, which has been analyzed within WNT in [38] and studied experimentally and by simulations in [39][40][41]. Physical realizations of one-dimensional interfaces occur, e.g.…”
Section: A([h] T) ≡mentioning
confidence: 99%
“…[37] and studied experimentally and by simulations in Refs. [38][39][40]. Physical realizations of onedimensional interfaces occur, e.g., in lipid bilayer membranes below their demixing transition [41,42].…”
Section: Introductionmentioning
confidence: 99%